Determinasi Produktivitas Kerja: Flexible Working Space, Transformational Leadership dan Organizational Culture - Sri Widiyati; Amalia Fitri Dwi Widyati; Dewi Mariana (STKIP PGRI SITUBONDO, 2022)
Corona Virus Disease-2019 is a virus outbreak that is spreading across the country. It is caused by the coronavirus, which has been known to harm the respiratory system. Indonesia then proclaimed COVID-19 a global pandemic and advised citizens to perform physical distancing. COVID-19 affects not only health but also social, economic, and labor aspects. This study aims to examine the critical elasticities affecting work productivity in the Covid-19 pandemic period, specifically: Flexible Working Space, Transformational Leadership, and Organizational Culture. Qualitative methodologies and a literature review were employed in the research. The data sources include journals that are indexed by Google Scholar and book literature. The researchers confirmed that Flexible Working Space, Transformational Leadership, and Organizational Culture affect Work Productivity.